Innovating for success in the export of services : a handbook (ITC GenevaCH, 1999)
Deals with services innovation as a tool for enhancing export profitability. Approaches innovation as a competitive strategy. Describes characteristics of services innovation and its relation with cultural variables. Outlines guidelines for establishing appropriate innovation. Explains how to review quality assurance procedures and clarify customer priorities. Reviews the implementation cycle. Examines innovations links to export readiness.
DC